Influence of friction stir welding tool geometry on tensile strength of the joint - Tadeusz Balawender; Łukasz Micał (Advances in Mechanical and Materials Engineering, 1970)
Due to specific mechanical properties 2024 aluminum alloy is ideally suited for application in aerospace and automobile industries and because of its poor weldability is not widely used in other industries. To overcome this problem, a series of friction stir welding (FSW) experiments were conducted on 2024 aluminum alloy sheets by varying tools and key parameters of the process, i.e., rotation speed and travel rate of the weld tool. To investigate the influence of FSW process parameters on the mechanical strength of the joint, the tensile strength of the joint was examined as a function of FSW parameters for each tool. Optimum values of tool rotation speed and advance speed were determined for each tool and finally the optimum tool has been found.